Exposure of cancer cells to heat shock protein inhibitors induces decreased tumour survival - Burgos-Molina, Antonio Manuel; Peinado-Ruiz, Isabel C.; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (My University, 2022)
All tumour studied show an increase in resistance to treatment and an increase in cell survival. This response is related to an increase in the heat shock protein HSP90, since it participates in the assembly of telomerase, causing telomeres not to be shortened and leading to a longer cell life. When an HSP90 inhibitor is administered together with the usual treatment of this type of tumours, a decrease in cell survival and resistance to the antineoplastic treatment was observed. Recent scientiﬁc and clinical data show that HSP90 inhibitors strongly affect the survival of cancer cells and their use in combination with anticancer agents makes it possible to postpone cellular resistance to chemotherapy.
Keywords: Tumores - Investigación; Heat shock protein inhibitors; Tumour survival; HSP90 inhibitors